The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s00330-014-3377-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of contrast-enhanced ultrasound in the study of hepatic artery hypoperfusion shortly after liver transplantation: contribution to the diagnosis of artery steal syndrome

Abstract: • CEUS is useful in the diagnostic work-up shortly after liver transplant • CEUS identifies the hepatic artery thrombosis with reliability • There is little information about DUS and CEUS findings in the ASS • DUS and CEUS offer functional information useful in the diagnosis of ASS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 29 publications
1
22
1
Order By: Relevance
“…Contrast material-enhanced US has proven to be an important tool in assessment of the graft vasculature as well as the liver parenchyma and may obviate angiography and cross-sectional imaging methods (21,22). Nevertheless, it is not yet widely used in clinical practice for standard evaluation after liver transplant.…”
Section: Imaging Modalities Ultrasonographymentioning
confidence: 99%
“…Contrast material-enhanced US has proven to be an important tool in assessment of the graft vasculature as well as the liver parenchyma and may obviate angiography and cross-sectional imaging methods (21,22). Nevertheless, it is not yet widely used in clinical practice for standard evaluation after liver transplant.…”
Section: Imaging Modalities Ultrasonographymentioning
confidence: 99%
“…The presence of a hepatic arterial diastolic reversal waveform or a high RI has not been reported in these conditions. It has been reported that splenic steal syndrome can cause a substantial decrease in blood flow and may also lead to the misdiagnosis of thrombosis on Doppler sonography 6 , 24 , 25 . However, none of our splenic steal syndrome cases were reported as being misdiagnosed as hepatic artery thrombosis cases on Doppler sonography because the hepatic artery was visualized on Doppler sonography in all patients.…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, the number of Doppler sonograms obtained varied among patients, which may have affected our results. Contrast‐enhanced sonography has been used to detect vascular complications after orthotopic liver transplantation and has proved to be useful in identifying hepatic artery thrombosis and splenic steal syndrome 25 , 26 . However, ultrasound contrast agents have not been applied clinically in this country.…”
Section: Discussionmentioning
confidence: 99%
“…Some included studies restricted the interpretation protocol in order to reduce the chance of a misdiagnosis. CEUS was not performed if there were no available trained radiology staff in the study of Garcacriado (25). More than one experienced examiner was involved in analyzing the CEUS scan in order to avoid misreading in the study performed by Rennert and Zheng (32,34).…”
Section: Discussionmentioning
confidence: 99%
“…Relevant data extracted from all 13 studies are summarized in table 1 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Only two studies involved more than 100 cases for CEUS evaluation.…”
Section: Study Characteristicsmentioning
confidence: 99%